Antibacterial Activity of the Polymeric Form of Josamycin - E. D. Nikolskaya; O. A. Zhunina; M. B. Sokol; M. V. Fomicheva; N. V. Gukasova; E. A. Vorontsov; N. G. Yabbarov; O. G. Tereshchenko; E. S. Severin (Антибиотики и Химиотерапия, 2020)
The polymeric form ofjosamycin was developed by loading of the antibiotic into spherical submicron particles made of poly(DL- lactide-co-glycolide) (PLGA 50/50) by double emulsion method. The average diameter and zeta-potential of particles synthesized were less than 150 nm and -35 mV respectively. Polymeric form showed antimicrobial activity against gram-positive, gram-negative, and atypical bacteria. The highest antibacterial activity compared to substance (more than 8-fold) was detected against Enterococcus faecalis. The results of in vivo studies of specific activity of drugs on the model of staphylococcal sepsis in mice showed an increase in the efficacy of the studied polymeric form by 1.5-fold compared with the josamycin substance.